Characterization of gibberellin 2-oxidase isoforms in coconut (Cocos nucifera L.) - Rahman, Shafeeq; Gangaraj, K.P.; Vasu, Amal; Karun, Anitha; Rajesh, M.K. (Journal of Plantation Crops, 2015)
<span style="line-height: 107%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-bidi-language: HI; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-fareast-language: EN-US;" lang="EN-GB">Gibberellins (GAs) are plant hormones that are essential for many developmental processes in plants, including seed germination, stem elongation, leaf expansion, trichome development, pollen maturation and the induction of flowering. Gibberellin 2-oxidase (GA2-ox) regulates plant growth by inactivating endogenous bioactive GAs through 2Î²-hydroxylation. There is no information about GA2-ox encoding genes or their functions in coconut. In this study, we have identified 10 transcripts encoding different isoforms of GA2-ox from coconut leaf transcriptome data. Sequence comparison and phylogenetic analysis revealed that these 10 transcripts represented different types of GA2-ox. The secondary structure, three dimensional structure and active sites of these 10 isoforms were predicted. Docking studies of different active GAs with these isoforms was also carried out.